2022
DOI: 10.1038/s41467-022-35117-4
|View full text |Cite
|
Sign up to set email alerts
|

Human visual consciousness involves large scale cortical and subcortical networks independent of task report and eye movement activity

Abstract: The full neural circuits of conscious perception remain unknown. Using a visual perception task, we directly recorded a subcortical thalamic awareness potential (TAP). We also developed a unique paradigm to classify perceived versus not perceived stimuli using eye measurements to remove confounding signals related to reporting on conscious experiences. Using fMRI, we discovered three major brain networks driving conscious visual perception independent of report: first, increases in signal detection regions in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 68 publications
5
31
1
Order By: Relevance
“…In addition, a recent electrophysiological study of rhesus monkeys using the no-report paradigm also found that even without the requirement of explicit reporting, awareness-related neurons can still be found in the lateral prefrontal cortex of rhesus monkeys, and conscious content can be accurately decoded by the MVPA method 36 . Another human fMRI study also found similar results 17 . These results supported our experimental results.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In addition, a recent electrophysiological study of rhesus monkeys using the no-report paradigm also found that even without the requirement of explicit reporting, awareness-related neurons can still be found in the lateral prefrontal cortex of rhesus monkeys, and conscious content can be accurately decoded by the MVPA method 36 . Another human fMRI study also found similar results 17 . These results supported our experimental results.…”
Section: Discussionsupporting
confidence: 57%
“…There is growing evidence showing that conscious experience may be represented at the brain network level 17,21 . Thanks to the simultaneously recorded LFP data in multiple brain regions with a high signal-to-noise ratio and high spatial-temporal resolution, we can analyze the dynamic functional connectivity changes under the aware and unaware conditions at the millisecond scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N200 peak times are commonly found between 150 and 250 ms post onset [60][61][62][63] , so to get the onset of the wave, an earlier time window was used. However, this does lead to potential overlap with the N100 ERP 31 and the end of the window may overlap with the P300 ERP 64 . Visualization of the trial averages (Fig.…”
Section: Discussionmentioning
confidence: 99%